(الوقف والابتداء في القرآن الكريم والاستفادة منهما في تعليم اللغة العربية (سورة القمر نموذجا - Aniroh Febriyani (Rayah Al-Islam, 2019)
This research was aimed to identify waqf (the pause-the place where we may stop reading) and ibtida (the start- the place where we can start reading after the pause) and its application in the teaching of Arabic by taking example from al-Qur’an surah al-Qomar. Waqf and ibtida are among the important knowledge that should be learnt in order to help the reciter of al-Qur’an or the student of Arabic to get well understanding of al-Qur’an and Islamic knowledge, and to avoid mistakes we found in conversation or the reading that may cause incorrect meaning. The research used descriptive analytical method by collecting information and data related to the topic research. The qualitative analysis was used in Miles and Huberman and consists of four steps, including data collection, data reduction, data presentation, and conclusion. Result of the research proved that waqf and ibtida have a big relation in changing the meaning of an ayah: firstly, waqf that agrees with the meaning of ayah in surah al-Qomar reach fourty-four ayat and secondly, waqf between the bad and the good in surah al-Qomar reach eleven ayahs.. For this, research formulate effective way to practice through conversation and reading.